Implementation of Project-Based Learning in an Effort to Increase Social Awareness through Alms Activities in Class IV SDN 002 Rambah Hilir - Fitri, Umi; Leni, Mesis (STKIP Rokania Pasir Pangaraian, 2024)
This study aims to implement project-based learning in increasing students' social awareness through alms activities in grade IV of elementary school. The research approach used is Classroom Action Research, which consists of two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subject of the study was 20 grade IV students of an elementary school in Negeri 002 Rambah Hilir Riau in the subject of Islamic Religious Education. The results of the study show that the application of project-based learning through alms activities is able to increase students' understanding and awareness of the importance of sharing with others. In addition, there was an increase in the cognitive, affective, and psychomotor aspects of students that were related to the value of social care. Thus, project-based learning can be an effective strategy to instill the character of social care in elementary school students.